Analisis Risiko Operasional dan Penerapan Manajemen Risiko pada CV XYZ di Kota Pekanbaru - Yovanna Nabila Azzahra; Ilma Amelia; Olipian Resky Pernando; Nur Azizah (Master Manajemen, 2025)
This study aims to analyze the form of operational risk faced by CV XYZ, a used car buying and selling business in Pekanbaru City, and to evaluate the extent to which risk management is implemented in its operational activities. This study uses a qualitative descriptive approach with a case study method. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation. The results of the study indicate that CV XYZ faces various operational risks, including hidden damage to vehicles, document legality issues, and suboptimal customer service. The implementation of risk management is still informal, undocumented, and does not follow certain standards such as ISO 31000. Risk handling is carried out intuitively and reactively, not preventively. However, there is awareness from the management to start building a more structured risk management system through the preparation of SOPs and evaluation of internal processes. This study emphasizes the importance of implementing systematic risk management for small and medium businesses in order to be able to compete sustainably and maintain customer trust.